Evaluation of Community-based Settlement Reconstruction Program (Case Study in Post-Disaster Recovery of 2010 Merapi Volcano Eruption in Cangkringan District, Sleman Regency, Yogyakarta Special Region) - Dwi Samekto, Christ Bangun (JPAS (Journal of Public Administration Studies), 2017)
Merapi eruption in 2010 destroyed 3,083 houses in Sleman Regency. After passed through emergency phase, Government of Indonesia conducted resettlement reconstruction program for 2,083 houses in Sleman Regency.. This study aims to evaluate the settlement reconstruction program after Merapi 2010 eruption in Cangkringan District, Sleman Regency Yogyakarta province by factors abstracted from previous researches. Field survey held with the household questionnaires distributed to communities to evaluate the program by factors abstracted before. This study found out that community empowerment and community oriented, transparency and accountability, coordination of stakeholders are the supporting factors for Merapi 2010 eruption resettlement program. Meanwhile, Social condition of beneficiaries and miss-perception about Community-Based Settlement Reconstruction identified as constraining factors in this program.